Cityhood, good governance, and local development case of Victorias City, Negros Occidental. - Nifras, Francis Ariel G
This paper analyzes the processes involved in the conversion of a municipality into a city and provides a qualtative evaluation of the impacts of cityhood on governance and local development. The process of conversion of Vicrtorias from municipality into a city involved interactions of politicians,bureaucrats and interest groups, and the relative bargaining power of each group influences the final outcome., All in all, the conversion of Victorias from a municipality into a city had positive effects on governance and local development.